Dinâmica da matéria orgânica em solo tratado com resíduos orgânicos nos Tabuleiros Costeiros do Estado de Sergipe - Moura, Juliana Augusta (2013)
In the state of Sergipe, more precisely in the center-south region of the Coastal Plains serves as the stage for one of the largest citrus production in the country. The intensive cultivation of these soils reduces the content of organic matter that is the key component to ensure its quality. Thus, the use of alternate layering residues format, can be a viable alternative to the revitalization of citrus orchards. The objective of this study was the evaluation of the labile and stable soil organic matter, carbon management index and microbial activity in soil treated with organic waste and citrus cultivation in the state of Sergipe. Soil samples were collected in the layers 0-5 cm, 5-10 cm, and 10-15 cm in a citrus (Citrus sinensis, L. Osbeck) orchard treated either with organic residues or mineral fertilizer, or a combination of the two (conventional management, where the projection of the plant canopy was kept clean of weeds, and no mineral fertilization; humus residues; alternate layering residues (in situ made compost); alternate layering residues + NPK; only NPK; humus residues + NPK; and a native forest soil as reference). The results were submitted to analysis of variance and means were compared by the Scott-Knott test at 5% probability by the software SISVAR. To evaluate the microbial activity was also determined the coefficient of correlation (p . 5) via the computer application SAEG. The study of C in the labile and stable organic matter were more effective than isolated evaluation of total organic carbon (TOC) to check for changes in the dynamics of C in the soil. The C in particulate organic matter (C-POM) was more sensitive than the content of C in complexed organic matter (C-COM). Overall, the treatments that have provided incorporation of organic residues showed carbon management index (CMI) close to the native forest. The fulvic acids fraction (FAF) helped identify the changes in soil for different types of management. The humin fraction (HUMF) showed the highest levels of C relative to FAF and humic acids fraction (HAF). The incorporation of organic waste to the crowning of the orange zone also caused an increase in microbial respiration rates, in total content of organic matter, as well as the elevation of pH, P, Ca and Mg treatments when compared to native forest and conventional management. The ratio stratification was effective to evaluate the influence of different management practices between depths indicating treatments Humus, Humus + NPK and altenate layering residues + NPK as the most effective in increasing the organic matter content in the soil. The benefits caused to soil after the incorporation of organic waste show that the use of practices more conservationist contributes to the improvement of the soil.